Ferroptosis is involved in alcohol-induced cell death in vivo and in vitro. Issue 8 (2nd August 2020) - Liu, Chun-Yu; Wang, Min; Yu, Hong-Min; Han, Fang-Xuan; Wu, Qiong-Shi; Cai, Xing-Jun; Kurihara, Hiroshi; Chen, Yong-Xing; Li, Yi-Fang; He, Rong-Rong
ABSTRACT: A critical pathogenic factor in the development of lethal liver failure is cell death induced by the accumulation of lipid reactive oxygen species. In this study, we discovered and illuminated a new mechanism that led to alcoholic liver disease via ferroptosis, an iron-dependent regulated cell death. Study in vitro showed that both necroptosis inhibitor and ferroptosis inhibitors performed significantly protective effect on alcohol-induced cell death, while apoptosis inhibitor and autophagy inhibitor had no such effect. Our data also indicated that alcohol caused the accumulation of lipid peroxides and the mRNA expression of prostaglandin-endoperoxide synthase 2, reduced the protein expression of the specific light-chain subunit of the cystine/glutamate antiporter and glutathione peroxidase 4. Importantly, ferrostatin-1 significantly ameliorated liver injury that was induced by overdosed alcohol both in vitro and in vivo . These findings highlight that targeting ferroptosis serves as a hepatoprotective strategy for alcoholic liver disease treatment. Abstract : uf0001 Excessive consumption of alcohol induces the ferroptosis of hepatocytes via catalyzing lipid peroxidation.